Library strategic environment in the public cultural service system in China: A case study of Yunnan Province. Issue 4 (13th June 2016) - Ke, Ping; Chen, Xin; Liu, Yingxi; Zhao, Yimin
Abstract : Purpose: – China is currently constructing the public cultural service system on a national scale. Library strategic environment problems, such as the status of library in the public cultural service system, the relationship with relevant public cultural service institutions/organizations, and the factors influencing library development, etc., which increasingly raise people's concern. The purpose of this paper is to solve above mentioned problems. Design/methodology/approach: – This paper used online and offline questionnaires to solicit feedback from public cultural service institutions/organizations. Based on the data from questionnaires, this paper analyzed library strategic environment in the public cultural service system in mainland China by adopting correlation analysis, mean analysis and factor analysis, etc. Findings: – Stakeholders (relevant public cultural service institutions) highly valued the status of library and no respondents believed that library did not belong to the public cultural service system. Compared with competing relationship between enterprises, library and relevant cultural services institutions were partners rather than competitors. Three main factors that influenced library strategic planning were identified: internal conditions factors, external environment factors and stakeholder related factors. Research limitations/implications: – There are some limitations of this thesis. For instance, the sample size is not large enough and respondents are confined to cities, which may reduce the generalizability of the findings. Originality/value: – Through this analysis, library can learn more of national cultural environment in China, and take necessary measures to cope with these changes.